Liquid Biopsy Using Whole Blood from Testis Tumor and Colon Cancer Patients—A New and Simple Way?. Issue 1 (July 2018) - Majewski, Matthäus; Nestler, Tim; Kägler, Sebastian; Richardsen, Ines; Ruf, Christian G.; Matthies, Cord; Willms, Arnulf; Schmelz, Hans-Ulrich; Wagner, Walter; Schwab, Robert; Abend, Michael
Abstract : Abstract: Tumor cells shed exosomes, which are released to the blood. Detecting tumor-derived exosomes containing RNA in plasma (liquid biopsy) is currently being investigated for early identification of occult metastases or relapses. Isolation of exosomes is laborious, resulting in low RNA yields. As a more robust (but less sensitive) alternative, the authors examined whether whole blood can be used as well. Tumor samples from nonmetastasized seminoma ( n = 5) and colon cancer patients ( n = 6) were taken during surgery. Whole-blood samples were taken before and 5–7 d after surgery. A whole genome mRNA microarray screening was performed. Candidate genes were selected based on two criteria: (1) gene expression in the presurgical whole-blood sample/tumor biopsy; and (2) a two-fold decrease in the copy number of candidate genes was expected in the postsurgical whole-blood sample 5–7 d after intervention, relative to the presurgical blood sample. The rationale behind this is the loss of tumor material in the body and the decline in the release of tumor-derived RNA in exosomes. For both tumor entities and for each patient, several hundred candidate genes could be identified. In a group-wise comparison, 20 candidate genes could be identified in the seminoma and 32 in the colon cancer group. These findings indicate that whole blood might be suitable for a liquid biopsy. However, this study identified the short period after surgery (5–7 d) as a possible confounder. The authors plan to add an additional time point several weeks after the operation to discriminate tumor candidate genes from genes induced by the surgery.